2DOF numerical investigation of a planing vessel in head sea waves in deep and shallow water conditions. (January 2019) - Masumi, Yasin; Nikseresht, Amir H.
Highlights: In displacement and semi-displacement regimes the drag force increases with decreasing the depth of water. In planing regime the drag force decreases with decreasing the depth of water. The intensity of drag force fluctuation increases with decreasing the water depth and wavelength and increasing the speed. Generally, it seems that λ / L = 4 is a critical point for the vessel. The maximum amplitude of the drag oscillation in wave is less than the maximum amplitude of the drag oscillation in porposing phenomenon. Abstract: Analysis of a craft with two degrees of freedom (2DOF) consumes time more than simulation of a craft with a fixed trim condition; therefore in most of the previous researches fixed trim condition is taken into account to analyze the flow field around a craft in shallow water and head sea wave conditions. In this paper numerical simulation of Reynolds Average Naiver Stokes (RANS) equations are used to analyze the motion of DTMB 62 model 4667-1 planing vessel in calm water and head sea waves in both deep and shallow water with two degrees of freedom (heave and pitch). For this purpose, a finite volume ANSYS-FLUENT code is used to solve the Navier-Stokes equations for the simulation of the flow field around the vessel. In addition, an explicit VOF scheme and SST k -ω model is used with dynamic mesh scheme to capture the interface of a two-phase flow and to model the turbulence respectively in the 2DOF model. Regarding the results, reducing the wavelength and also the depth of the water can increase the drag force. Also comparing the results of a fixed trim vessel with the results of a free to sink and trim one in calm water shows a difference of approximately 50% in the drag force in shallow water.